Implicatures Used in The House With A Clock in Its Walls (2018) - Yanti Purwaningsih (Faculty of Language and Literature, Universitas Sains Al-Qur'an, 2019)
The aims of this research are to analyze the utterances which is containing implicatures used in a movie entitled The House With A Clock in Its Walls (2018) and its functions. In this research, the researcher try to analyze types of implicaturesused in The House with A Clock in Its Walls (2018). Then, in the second problem statement, the researcher analyze the functions of implicatures that found in the movie entitled The House with A Clock in Its Walls (2018). This research is categorized as qualitative research. As the result, the researcher concludes that the types of implicatures and the functions are founded in the movie entitled The House with A Clock in Its Walls (2018). The result shows that there are four types of implicatures. They are generalized conversational implicature, scalar implicature, particularized conversational implicature, and conventional implicature. There are also some functions of implicatures found in doing this research. They areassertives, directives, commissives, and expressives.